2010
DOI: 10.2176/nmc.50.1031
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Primitive Neuroectodermal Tumor Presenting With Rapidly-Progressive Cauda Equina Syndrome -Case Report-

Abstract: A 39-year-old male presented with gait disturbances with rapid deterioration for 2 weeks. Neurological examination found paraparesis, sensory loss in the L1-S5 dermatomes, and vesicorectal dysfunction. Magnetic resonance (MR) imaging revealed a fusiform intramedullary tumor at T12-L1 levels with heterogeneous enhancement. The patient underwent microsurgical tumor resection. A myelotomy exposed a highly vascular tumor that was subtotally resected. Histological examination demonstrated hypercellular tumor accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…The identified cases showed that intramedullary Ewing sarcoma was located mainly in the thoracic and lumbar regions, although cervical and sacral locations were also reported. 4 36 The current case had a thoracic intramedullary lesion and a lumbar extramedullary lesion, both causing neural compression and deficits.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The identified cases showed that intramedullary Ewing sarcoma was located mainly in the thoracic and lumbar regions, although cervical and sacral locations were also reported. 4 36 The current case had a thoracic intramedullary lesion and a lumbar extramedullary lesion, both causing neural compression and deficits.…”
Section: Discussionmentioning
confidence: 87%
“… 2 The prognosis and survival rate for patients with spinal cord Ewing sarcoma is not well known because of the rarity of the condition; however, based on previous cases ( Table 1 ), the survival rate was 45% to 50% in primary cases and 30% to 35% in recurrent and metastatic cases. 4 36 In surviving cases, rehabilitation and physical therapy should be considered part of the treatment program to improve the patient’s neurological status. In the current case, the patient improved markedly after 4 months of physical therapy and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle uzun dönemli kontrolü amaçlamaktan çok hastanın hayat kalitesini ön plana alarak, tedaviye bağlı toksisiteden kaçınarak tedavi planlamak önerilebilir. [24] Sonuç olarak, daha az agresif tedavi ile toksisiteden kaçınmak bir alternatif olarak değerlendirilmelidir. Hastamızda total rezeksiyon sonrası kraniyospinal radyoterapi uygulanmıştır.…”
Section: Discussionunclassified
“…[ 4 ] Primary spinal PNETs are uncommon and can be extradural, intradural extramedullary, and intramedullary, of which primary intramedullary PNETs are extremely rarer. [ 5 , 6 ] Till now, only 24 cases of primary intramedullary PNETs have been reported. [ 3 , 5 24 ] Here we describe an unusual case of primary intramedullary PNET with unique clinical features and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%